1984
DOI: 10.2170/jjphysiol.34.295
|View full text |Cite
|
Sign up to set email alerts
|

A new indirect method for measuring arteriovenous O2 content difference and cardiac output from O2 and CO2 concentrations by rebreathing air.

Abstract: A new indirect method for measuring the arteriovenous 02 content difference (avDo 2) was developed. The avDo 2 was calculated by dividing the gradient of the C02 dissociation curve by that of a gas exchange ratio against Pco2. The latter slope was obtained from 02 and C02 concentrations in rebreathing air. The validity of the method was tested preliminarily in human subjects by comparing the cardiac output calculated from avDo 2 and 02 uptake (o2) with that measured hitherto by other authors, and then in dogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…KAGAWA and MOCHIZUKI (1987) designated the (a-v)Co2 at the PAco2, where the pH~ in arterial blood equals that in venous blood, as the standard (a-v)Co2 ((a-v)Co2*). Furthermore, they developed a method to obtain the (a-v)Co2* by a modification of the method originated by MOCHIZUKI et al (1984). Let the middle between trPvco2 and oxPvco2 be Pm2 and the slope of the C02 dissociation curve at Pmt be a'(Pm2) (vol%.Torr-1).…”
Section: Derivation Of Contact Time Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…KAGAWA and MOCHIZUKI (1987) designated the (a-v)Co2 at the PAco2, where the pH~ in arterial blood equals that in venous blood, as the standard (a-v)Co2 ((a-v)Co2*). Furthermore, they developed a method to obtain the (a-v)Co2* by a modification of the method originated by MOCHIZUKI et al (1984). Let the middle between trPvco2 and oxPvco2 be Pm2 and the slope of the C02 dissociation curve at Pmt be a'(Pm2) (vol%.Torr-1).…”
Section: Derivation Of Contact Time Equationmentioning
confidence: 99%
“…Moreover, let the slope of the R-P02 line obtained from gas analysis of rebreathing air be 6. MOCHIZUKI et al (1984) estimated the (a-v) Cot by dividing the a'(Pm2) by 8. Since the (a-v)Co2 thus obtained, however, was not accurate enough, KAGAWA and MOCHIZUKI (1987) derived a correcting factor (F(H)) from the numerical solution of 02 and C02 diffusions in the RBC and attempted to estimate the (a-v)Co2*:…”
Section: Derivation Of Contact Time Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…KAGAWA and M. MOCHIZUKI MocHIZUKI et al (1984) derived an equation to determine the arterial-venous 02 content difference ((a-v)Co2) from the a' and the slope of a gas exchange ratio versus the Pco2 in rebreathing air (9), as given by (a-v)C02 = a'/0. When the C02 equilibrium is not reached, the (v-a)Cco2(H) becomes less than the product of a' • (oxPvco2 -trPvco2).…”
mentioning
confidence: 99%
“…It has been reported that a comparison between the Q values determined by this method and the direct Fick method results in a correlation coefficient of 0.88 in dogs (MOCHIZUKI et a!.,1984). Mixed venous tension of C02 (Pvco2) was determined from the above R-Pco2 replationship by taking the point when R = 0, and converting it into terms of the concentration in the blood (CV02) ~by reading off the C02 dissociation curve.…”
Section: Methodsmentioning
confidence: 99%